Human resource management : a critical approach - Collings, David G.; Wood, G. (London ; New York : Routledge, 2009)
Effective management of human resources is essential to the success of any organization. The book explores all the central themes and concepts of HRM theory and practice, and introduces the most important issues influencing contemporary practice in a wide range of organizational contests. It systematically examines the main functional areas of HRM and engages with a number of key contemporary issues for both scholars and practitioners.
Includes bibliographical references and index.
nmn 4/06/13
Loans
Keywords: Personnel management; Human resource management